Role of tau deposition in early cognitive decline in Down syndrome. Issue 1 (1st April 2022) - Hartley, Sigan L.; Handen, Benjamin L.; Tudorascu, Dana; Lee, Laise; Cohen, Annie; Piro‐Gambetti, Brianna; Zammit, Matthew; Klunk, William; Laymon, Charles; Zaman, Shahid; Ances, Beau M.; Sabbagh, Marwan; et al.
Abstract: Introduction: Drawing on the amyloid/tau/neurodegeneration (AT[N]) model, the study examined whether the tau positron emission tomography (PET) biomarker [ 18 F]AV‐1451 was associated with episodic memory problems beyond what was predicted by the amyloid beta (Aβ) PET in Down syndrome (DS). Methods: Data from 123 non‐demented adults with DS ( M = 47 years, standard deviation = 6.34) were analyzed. The Cued Recall Test assessed episodic memory. Tau PET standardized update value ratio (SUVR) was assessed across Braak regions as continuous and binary (high tau [TH ] vs. low tau [TL ]) variable. Global PET Aβ SUVR was assessed as binary variable (Aβ– vs. Aβ+). Results: In models adjusting for controls, tau SUVR was negatively associated with episodic memory performance in the Aβ+ but not Aβ– group. The Aβ+/TH group evidenced significantly worse episodic memory than the Aβ+/TL group. Discussion: Similar to late‐onset and autosomal dominant Alzheimer's disease (AD), high tau was an indicator of early prodromal AD in DS.